Internal Communication Strategy of PT. Duta Sentosa Yasa in Maintaining a Good Relationship Between Leadership and Employees - Ikhsan Novendra; Robbikal Muntaha Meliala; George Wilhelm Bender (Jurnal Multidisiplin Sahombu, 2026)
PT Duta Sentosa Yasa, known as the warehouse and distribution center for MR.DIY in Indonesia with the Marunda Warehouse & Distribution Centre, plays a key role in ensuring the smooth operation of the company. This study aims to analyze the internal communication strategy implemented by PT Duta Sentosa Yasa in maintaining good relationships between management and employees, as well as to evaluate the employee relations program at the Marunda warehouse. The research method used is descriptive qualitative, with data collection through observation, interviews, documentation, and literature review. The results show that the internal communication strategy at PT Duta Sentosa Yasa has been effective in building mutual trust between management and employees, creating a productive work environment. The use of vertical, diagonal communication, and digital media such as WhatsApp ensures clear and efficient information flow. Vertical communication allows for two-way dialogue, while diagonal communication strengthens interdepartmental collaboration. Additionally, the company focuses on the employee relations program by improving productivity and job satisfaction through open communication and regular social activities. However, evaluation of certain elements reveals shortcomings, such as the lack of a systematic annual health evaluation. The implementation of periodic health evaluations could enhance the effectiveness of internal communication strategies and employee well- being.